Radical-Scavenging and Anti-Oxidative Activities of TBN in Cell-Free System and Murine H9c2 Cardiomyoblast Cells - Zhu Longjun; Sun Yewei; Zhang Gaoxiao; Yu Pei; Wang Yuqiang; Zhang Zaijun (Journal of Antioxidant Activity, 2015)
Reactive oxygen species (ROS) and reactive nitrogen species are believed to be one of the most important culprits in the pathogenesis of cardio/cerebrovascular diseases. Intensive researches have been conducted to target free radicals as potential treatment for cardio/cerebrovascular diseases. The 2-(((1,1-dimethylethyl) oxidoimino)-methyl)-3,5,6-trimethylpyrazine (TBN), a novel nitrone derivative of tetramethylpyrazine, has been demonstrated to exhibit significant therapeutic effects in ischemic stroke and Parkinson’s models due to its multiple functions, including calcium overload blockade and free radical-scavenging activity. In the present study, we found that TBN had significant radical trapping effect in cell-free assays. Additionally, TBN effectively blocked tert-butylhydroperoxide (t-BHP)-induced murine H9c2 cardiomyoblast cell death, suppressed H9c2 cell apoptosis and reversed the decrease in mitochondrial membrane potential. Furthermore, TBN markedly inhibited t-BHP-induced ROS generation and free radical NO and ONOO–.Taken together, these results suggest that TBN might be a potential candidate for the treatment of ischemic cardio/cerebrovascular diseases by targeting free radicals.
Keywords: Tetramethylpyrazine